Čačak and its daily urban system: Second part - Stamenković Srboljub Đ.; Gatarić Dragica R. (Glasnik Srpskog Geografskog Društva, 2007)
In this article, which is an integral part of our announcement published in the previous number of this publication, we examined commuting of school children and youth toward Čačak as well as from Čačak toward surrounding settlements in which, according to the census results in 2002, 2,330 pupils and students took part. The volume of pupils’ and students’ daily migrations of Čačak is approximately 4.3 times lower compared to the convergent and divergent daily migrations of its labor. That is why this type of continual daily migration has less importance in integration and transformation of the settlement network of Čačak and neighboring functional centers.